The Prae-Adamitae and the early Royal Society: two cases from the periphery - Poole, W (2004)
Isaac La Peyrere’s Prae-Adamitae (1655) and Socinian tendencies in the early Royal Society: some manuscripts of Francis Lodwick (1619-1694) and Francis Willughby (1635-1672). The hypothesis that there were men before Adam was most notoriously mooted by the dissident Calvinist Isaac La Peyrère, who was circulating his views in manuscript in French intellectual circles from the early 1640s. The full version of his theory became internationally available in 1655 with the publication in Latin of his expanded Prae-Adamitae, translated into English the following year, and into Dutch in 1661. La Peyrère’s impact in England is hard to assess, and the various interregnum radical instances of the hypothesis do not appear to owe much to La Peyrère, nor indeed do they have much in common with each other. But La Peyrère’s book, despite the attempted banning of the English translation, circulated unimpeded in Latin, and is to be found listed in many library and sale catalogues of the period. The Prae-Adamitae was particularly popular in Royal Society circles, where La Peyrère was also read as the geographical authority on Iceland and Greenland. Robert Hooke and his friends discussed the Preadamite hypothesis in the coffee-shops in late 1675 – "To Martins and Garaways club: Ludowick, Hill, Aubery, Wild. Discoursd about Universal Character, about preadamits and of Creation" – and the book was owned, excerpted , or both, by F.R.S.s including Hooke, Edmund Halley, Abraham Hill, John Ray, Francis Lodwick, and Francis Willughby. This paper discusses two of the more interesting reactions among these men to the Preadamite hypothesis, those of Francis Lodwick, the language-planner, Royal Society administrator, and close friend of Robert Hooke; and of the naturalist and taxonomer Francis Willughby. Lodwick, perhaps surprisingly, supported the Preadamite hypothesis. Willughby, who summarised the work in his commonplace book, may not have assented directly to the hypothesis, but his papers do show that he was willing to entertain aggressively sceptical notions about the moral status of the Old Testament. Such an emphasis is compatible, as it is in Lodwick, with Socinian trends in biblical exegesis. Such activities disprove or at least severely compromise Thomas Sprat’s apologetical insistence in 1668 that the new science was the perfect handmaid for orthodox theology and ecclesiology.